Association between ASA grade and complication rate in patients receiving procedural sedation for relocation of dislocated hip prostheses in a UK emergency department. Issue 3 (14th February 2013) - Dawson, Neil; Dewar, Alistair; Gray, Alasdair; Leal, Alexis; ,
Abstract : Objective: To determine the association between the American Society of Anesthiologists (ASA) grade and the complication rate of patients receiving procedural sedation for relocation of hip prosthesis in an adult emergency department (ED) in the UK. Design: Retrospective study of registry data from a large UK teaching hospital ED. Consecutive adult patients (aged 16 years and over) in whom ASA grade could be calculated, with an isolated dislocation of a hip prosthesis between 8 September 2006 and 16 April 2010 were included for analyses (n=303). The primary outcome measure was association between ASA and complication rate (any of desaturation <90%; apnoea; vomiting; aspiration; hypotension <90 mm Hg; cardiac arrest). Secondary outcome measures were relationship between ASA grade and procedural success, choice of sedative agent and sedation depth, and complications and choice of sedative agent, arrival time and sedation depth. Results: There was no significant difference between ASA grade and the risk of complication (p=0.800). Moreover, there was no significant difference between ASA grade and procedural success (p=0.284), ASA and choice of sedative agent (p=0.243), or ASA and sedation depth (p=0.48). There was no association between complications and sedative agent (p=0.18), or complications and arrival time (p=0.12). There was a significant difference between sedative depth and complications (p<0.001). Conclusions: There is no clear association between a patient's physical status (ASA grade) and the risk of complications, chance of procedural success or choice of sedative agent in relocation of hip prostheses. There is a higher rate of complications with higher levels of sedation (p<0.001).